The Role of Neuroinflammation in Post-traumatic Epilepsy - Sun, Lei; Shan, Wei; Yang, Huajun; Liu, Ru; Wu, Jianping; Wang, Qun (Frontiers in Neurology, 2021)
Post-traumatic epilepsy (PTE) is one of the consequences after traumatic brain injury (TBI), which increases the morbidity and mortality of survivors. About 20% of patients with TBI will develop PTE, and at least one-third of them are resistant to conventional antiepileptic drugs (AEDs). Therefore, it is of utmost importance to explore the mechanisms underlying PTE from a new perspective. More recently, neuroinflammation has been proposed to play a significant role in epileptogenesis. This review focuses particularly on glial cells activation, peripheral leukocytes infiltration, inflammatory cytokines release and chronic neuroinflammation occurrence post-TBI. Although the immune response to TBI appears to be primarily pro-epileptogenic, further research is needed to clarify the causal relationships. A better understanding of how neuroinflammation contributes to the development of PTE is of vital importance. Novel prevention and treatment strategies based on the neuroinflammatory mechanisms underlying epileptogenesis are evidently needed. Search Strategy Search MeSH Terms in pubmed: “[“Epilepsy”(Mesh)] AND “Brain Injuries, Traumatic”[Mesh]”. Published in last 30 years. 160 results were founded. Full text available:145 results. Record screened manually related to Neuroinflammation and Post-traumatic epilepsy. Then finally 123 records were included.